Evaluation of substance use among high school students and related factors (subject city: kastamonu) - Kaçan Softa, Havva; Ulaş Karaahmetoğlu, Gülşen; Ergun, Semra (Journal of Dependence, 2015)
Objective: This study aims to evaluate the substance use of senior high school students and, examine related factors with substance use in the city of Kastamonu. Method: The population of the study consists of 950 high school seniors who have attended substance use seminar from 10 different schools in Kastamonu. And the sample of the study is formed by those 502 students who have accepted to attend the study. For the data collection, researchers developed a questionnaire form in accordance with the literature. The questionnaire is comprised of 37 questions that aim to determine students’ socio-demographic characteristics, substance use and dependence. Statistical analyses of the collected data were performed using descriptive statistical methods (frequency, percentage), Pearson Chi-Square Test and Fisher Exact test. Results: It has been found that 90.2 % of the participants were 17 years old and 52.4 of them were male; 46.9 % of 18-year-old students used alcohol at least once in their lifetime; boys had higher use of alcohol and substance compared to the girls; students living in the city had higher substance use than those living in the district and villages; and increase in monthly allowance was associated with increased alcohol intake. Conclusion: In this study, the frequency of alcohol and cigarettes use has been found high. Preventive and protective actions must be taken in order to reduce the use of alcohol, cigarettes and substances at the puberty.